Analysing the Socio-Personal and Economic Profile of MGNREGA Beneficiaries in Cooch-Behar District - Anamika Guha and G. Mazumder, (Indian Journal of Extension Education, 2017)
Rural development is the process of improving the quality of life and economic well-being of people living in relativelyisolated and sparsely populated areas. The need for rural communities to approach development from a wider perspectivehas created more focus on a broad range of development goals rather than merely creating incentive for agricultural orresource based businesses. The MGNREGA ranks among the most powerful initiatives ever undertaken fortransformation of rural livelihoods in India. The study was undertaken to analyse the socio-personal and economic profileof MGNREGA beneficiaries. The study was conducted in Kokoabari and Dakkhin Kalarayer Kuthi villages of CoochBehar-II block of Cooch-Behar district in West Bengal. Purposive as well as simple random sampling procedures werefollowed in the present study. The results showed high degree of female participation and more income generation in thevillages after the implementation of MGNREGA.